CASH RATIO, EARNING PER SHARE, DEBT EQUITY RATIO, RETURN ON INVESTMENT DAN PENGARUHNYA TERHADAP KEBIJAKAN PEMBAGIAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR PERIODE 2004 – 2009 - Nurmala Nurmala (Universitas PGRI Palembang, 2011)
This Research is purposed to find to examine and prove the influence of Cash Ratio, Debt Equity Ratio, Earning Per Share, and Return On Investment to Manufacture Dividend Distribution Policy at Indonesia Share Exchange in 2004 – 2009.The hypothesis submitted are; There’s a significant influence of Cash Ratio, Debt Equity Ratio, Earning Per Share and Return On Investment to Dividend Distribution Policy. This research population is Manufacture Company listed on Indonesia Share Exchange. Using this sampling purposive way, known that 26 (twenty six) sample of company always distribute its dividend from 2004 – 2009.This analyze is using double correlation to find the connection of each independent and dependent variable, and using test –t and –F to find the influence of each other simultantly.The result shown that; There’s a significant correlation of Cash Ratio, Debt Equity Ratio, Earning Per Share and Return On Investment to Dividend Distribution Policy. Key words: correlation, debt, dividend, policy